Triplet Excited States as a Source of Relevant (Bio)Chemical Information - Consuelo Jimenez, M.; A. Miranda, Miguel (Current Topics in Medicinal Chemistry, 2014)
The properties of triplet excited states are markedly medium-dependent, which turns this species into valuable tools for investigating the microenvironments existing in protein binding pockets. Monitoring of the triplet excited state behavior of drugs within transport proteins (serum albumins and α1-acid glycoproteins) by laser flash photolysis constitutes a valuable source of information on the strength of interaction, conformational freedom and protection from oxygen or other external quenchers. With proteins, formation of spatially confined triplet excited states is favored over competitive processes affording ionic species. Remarkably, under aerobic atmosphere, the triplet decay of drug@protein complexes is dramatically longer than in bulk solution. This offers a convenient dynamic range for assignment of different triplet populations or for stereochemical discrimination. In this review, selected examples of the application of the laser flash photolysis technique are described, including drug distribution between the bulk solution and the protein cavities, or between two types of proteins, detection of drug-drug interactions inside proteins, and enzyme-like activity processes mediated by proteins. Finally, protein encapsulation can also modify the photoreactivity of the guest. This is illustrated by presenting an example of retarded photooxidation.
Keywords: Drug